2017
DOI: 10.1016/j.jss.2016.08.063
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma: a biomimetic approach to enhancement of surgical wound healing

Abstract: Platelets are small anucleate cytoplasmic cell bodies released by megakaryocytes in response to various physiologic triggers. Traditionally thought to be solely involved in the mechanisms of hemostasis, platelets have gained much attention due to their involvement wound healing, immunomodulation, and antiseptic properties. As the field of surgery continues to evolve so does the need for therapies to aid in treating the increasingly complex patients seen. With over 14 million obstetric, musculoskeletal, and uro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 96 publications
2
54
0
3
Order By: Relevance
“…Some of the results from treatment of chronic wounds with PRP [107109] are similar to those we have discussed in relation to local application of rFXIII in CVLU [95]. Thus far, there have been no reports, at least to our knowledge, about the FXIII-A content of PRP or its contribution to the effects of PRP.…”
Section: Future Perspectives For Fxiii-a In the Field Of Dermatologysupporting
confidence: 66%
See 1 more Smart Citation
“…Some of the results from treatment of chronic wounds with PRP [107109] are similar to those we have discussed in relation to local application of rFXIII in CVLU [95]. Thus far, there have been no reports, at least to our knowledge, about the FXIII-A content of PRP or its contribution to the effects of PRP.…”
Section: Future Perspectives For Fxiii-a In the Field Of Dermatologysupporting
confidence: 66%
“…Platelet-rich plasma (PRP) is widely used for its beneficial effects in wound healing and rejuvenation via multiple actions, as it contains several different types of molecules such as growth factors and cytokines [107]. Some of the results from treatment of chronic wounds with PRP [107109] are similar to those we have discussed in relation to local application of rFXIII in CVLU [95].…”
Section: Future Perspectives For Fxiii-a In the Field Of Dermatologymentioning
confidence: 86%
“…There is a growing consensus for the positive effects of PRP as an adjuvant therapy to aid the healing of surgical wounds and injuries. In fact, the growth factors present in PRP are involved in every stage of wound healing [71][72][73] , and several reviews [74][75][76][77][78] , systematic reviews [79][80][81] , and clinical studies [82][83][84] have reported their involvement in enhanced soft-tissue healing outcomes. Our results did not show statistically significant differences in the SWAS scores between the groups because they both obtained the best possible score.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is not a precise consensus regarding platelet-rich plasma production and characterization. This lack of consensus also prevents a standard approach in the PRP [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Platelets: origin, structure, distribution, and their roles in hemostasis Platelets, discovered in the nineteenth century, are small, nucleus-free cytoplasmic cellular structures which are round or oval-shaped and have about 2 μm diameter and derived from megakaryocytes (a type of white blood cell) in the bone marrow [1]. These cellular structures were initially believed to be involved only in the hemostasis and pathological thrombus formation.…”
Section: Introductionmentioning
confidence: 99%